The Impact of Educational Resource Management on Teacher Motivation and Job Satisfaction - Hamsy, Annisa; Amiruddin, Amiruddin; Rosmalina, Rosmalina; Pulungan, Lilik Hidayat (EDUCTUM: Journal Research, 2024)
Educational resource management is the key to success in education management. If education is managed effectively and efficiently, it can be ensured that education can run well in accordance with its objectives. The impact obtained if educational resource management is managed properly will increase teacher motivation and job satisfaction in providing education and teaching to students. This study discusses the impact of educational resource management on teacher motivation and job satisfaction. The research method used is a literature study using content analysis techniques from articles and written works in the form of books that have been collected as research material. Based on the research, the conclusion that can be drawn is that educational resource management in improving achievement is a system approach in an effort to maximise competitiveness through continuous improvement (continuous) to obtain optimal value or quality for services, people, products and the environment by involving all elements and stakeholders of the organisation under a shared vision so that good management encourages motivation for teachers or educators in providing good education to their students.